Fatal anaphylactic reaction to intravenous gadobutrol, a gadolinium-based MRI contrast agent - Franckenberg, Sabine; Berger, Florian; Schaerli, Sarah; Ampanozi, Garyfalia; Thali, Michael (Radiology case reports, 2018)
We present the rare case of a fatal anaphylactic reaction to gadobutrol, a magnetic resonance imaging contrast agent, in a 42-year-old man. The patient underwent elective magnetic resonance imaging for diagnostic clarification of a suspicious finding in the abdomen. The patient had undergone contrast-enhanced computed tomography previously without the occurrence of any adverse effects. Adverse drug reactions in gadobutrol have a very low prevalence of 0.32%-3.5%, with serious adverse drug reactions in <0.1%. There are only a few cases of fatal anaphylactoid reactions to gadolinium-based contrast agents in general. However, if an anaphylactoid reaction occurs, it can present itself with a fulminant course within minutes.